The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1093/bja/ael339
|View full text |Cite
|
Sign up to set email alerts
|

Bedside prediction of the central venous catheter insertion depth

Abstract: When CVCs are inserted to a depth derived by adding the length between the needle insertion point and the clavicular notch and the vertical length between the clavicular notch and the carina, the CVC tip can be reliably placed near the carina level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 14 publications
0
51
0
Order By: Relevance
“…Although the ideal position of the catheter tip is controversial, location in the superior vena cava (SVC) just above the pericardial reflection on a conventional radiograph is considered ideal to minimize the risks of cardiac tamponade and venous thrombosis [11]. Although several techniques to localize the catheter-tip and rule out malposition after CVC/PICC insertion have been investigated [12][13][14][15][16][17], portable chest radiography is currently considered the gold standard in imaging. However, its accuracy relative to tip localization may well be overestimated [18].…”
Section: Introductionmentioning
confidence: 99%
“…Although the ideal position of the catheter tip is controversial, location in the superior vena cava (SVC) just above the pericardial reflection on a conventional radiograph is considered ideal to minimize the risks of cardiac tamponade and venous thrombosis [11]. Although several techniques to localize the catheter-tip and rule out malposition after CVC/PICC insertion have been investigated [12][13][14][15][16][17], portable chest radiography is currently considered the gold standard in imaging. However, its accuracy relative to tip localization may well be overestimated [18].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al 17 showed that the optimal catheter insertion length during right subclavian venous cannulation was 12.9 ± 0.9 cm, while Ryu et al 5 suggested that 13.8 cm (10.5---18.0 cm) of subclavian venous catheter insertion would be optimal when the infra-clavicular landmark approach was used. However, this fixed length does not consider height, the preferred insertion point of the practitioner, or the method of subclavian venous cannulation, all of which might influence the final location of the catheter tip.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the internal jugular vein and the subclavian vein can be found easily beneath the ipsilateral clavicular notch, which is the site of articulation with the sternal end of the clavicle and can be readily palpated by hand. 6,20 Therefore, in another study, 5 the carina served as a landmark of adequate subclavian vein insertion length together with an estimate of the insertion length, which was calculated on the basis of a chest radiograph taken before central venous catheter insertion by adding (i) the distance between the insertion point of needle to the ipsilateral clavicular notch to (ii) the vertical distance between the ipsilateral clavicular notch to the carina. However, this method has some limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, measurement errors of the projection, p.a. or a.p., due to the parallax effect in CXR are negligible [11,12].…”
Section: Carina-tip Length and Laterality Onmentioning
confidence: 99%